2018
DOI: 10.1079/pavsnnr201813015
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nutrient components and their concentrations in edible parts in vegetable families.

Abstract: Information on food composition including types and contents of nutrients and anti-nutrients is important for food and nutrition research. There is satisfactory information on established nutritive elements for various food groups. However, literature on anti-nutrient component generally scattered and scanty on few major food groups and commonly consumed plant parts. A better understanding of both the positive and negative qualities of vegetable component would help develop better evidence-based promotion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 183 publications
0
10
0
Order By: Relevance
“…Although some studies reported that the main site where the absorption of free oxalate is the small intestine [ 143 ]. Absorbed soluble oxalate may still bind calcium present in the blood vessels, and precipitate in the kidney or urinary tract leading to the formation of kidney or urinary tract stones [ 144 ]. The negative effect of oxalates on calcium absorption increases when the molar ratio of total oxalate: calcium is major than 9:4 and this occurs in spinach and rhubarb [ 145 ].…”
Section: Calcium Absorption From Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies reported that the main site where the absorption of free oxalate is the small intestine [ 143 ]. Absorbed soluble oxalate may still bind calcium present in the blood vessels, and precipitate in the kidney or urinary tract leading to the formation of kidney or urinary tract stones [ 144 ]. The negative effect of oxalates on calcium absorption increases when the molar ratio of total oxalate: calcium is major than 9:4 and this occurs in spinach and rhubarb [ 145 ].…”
Section: Calcium Absorption From Foodsmentioning
confidence: 99%
“…Phytic acid is a phosphorus-based substance, which is found in cereals, legumes, nuts and seeds, but the highest phytate content was found in soybean (~2 g/100 g) [ 88 , 144 ]. Phytic acid can bind calcium in the stomach (below pH 4), forming a soluble calcium-phytate complex [ 150 ].…”
Section: Calcium Absorption From Foodsmentioning
confidence: 99%
“…62 Oxalate had a strong ability to create insoluble particles via chelating different minerals, and vital micronutrients like iron, zinc and calcium. 63 In oral intake, oxalate constrained with minerals in the gastrointestinal route and limited their metabolism. Metabolism of oxalate happened in gastric, tiny colon and massive colon.…”
Section: Resultsmentioning
confidence: 99%
“…Although such advanced processing techniques are not found in the surveyed area, techniques that the locals use like frying, grilling, and, on some occasions, boiling, are methods that will to some extent take care of pathogens and may reduce water-soluble anti-nutrient contents like trypsin inhibitor and oxalate etc. present in some insects, as these methods are found effective for some plant foods ( 60 , 61 ). Scientifically monitored production systems and processing technology now available in many European and Asian countries still need to be developed for Benin ( 59 ).…”
Section: Discussionmentioning
confidence: 99%